REPRODUCTIVE BIOLOGY OF RIVER SWIMMING CRAB VARUNA LITTERATA - Fariedah F,; S Rahayu, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aims to obtain information on the reproductive biology of these species, especially on sex ratio, fecundity, ovarian development, and breeding season. The study was conducted from August 2022 to July 2023 on every full moon with the highest tide in the estuary of Bengawan Solo River, East Java, Indonesia. The obtained samples were placed in the freezer and identified, and a dissection was performed to observe the gonads. There were 617 crabs with an average sex ratio of 1 male to 1.9 females. Mean fecundity of V. litterata was 45350±3182 egg/individual. In each sampling period, there were always females that were maturing gonads. The ovaries of females during the study were the early developed (stage III), late developed (stage IV), and mature (stage V), and no females in the immature (stage I) or underdeveloped (stage II). The highest mean of the Gonadosomatic Index was 0.14±0.3, and the result figured that V. litterata was in stage V. The highest GSI value was in June and December. This study illustrates that V. litterata has the potential to spawn every month and continuously for almost a year, with peak spawning between November and January.